Unseen Strength: Dementia, the COVID-19 Pandemic, and the Resilient Hearts That Never Stopped Caring - Alice Yip; Jeff Yip; Zoe Tsui; Ka Man Rachel Yip (COVID, 2025)
This qualitative study explored the motivations for, and resilience of, family caregivers visiting family members with dementia in residential care homes (RCHs) in Hong Kong during the COVID-19 pandemic. Data for this qualitative descriptive study was obtained through audio-recorded, semi-structured, in-depth interviews with 25 family caregivers of individuals with dementia in RCHs. Following transcription, a thematic analysis was performed on the verbatim data. Three main themes emerged: (a) virtue of respect and filial piety; (b) family expectations and hopes; and (c) from red flags to resilience and rebuilding stronger relational bonds. The findings elucidate family caregiver motivations and resilience during RCH visits, offering crucial insights for healthcare policymakers. This can inform the design of care services and support to bolster the resilience of both caregivers and their relatives with dementia amidst ongoing global health-system pressures.